2001
DOI: 10.1097/00003226-200101000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Keratoprosthesis: Preoperative Prognostic Categories

Abstract: Outcome of the keratoprosthesis surgery varied markedly with preoperative diagnosis. Most favorable was graft failures in non-cicatrizing conditions, whereas Stevens-Johnson syndrome was the worst. Ocular cicatricial pemphigoid and chemical burns occupied a middle ground. The difference between the groups seemed to correlate with the degree of past preoperative inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
2
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(159 citation statements)
references
References 5 publications
12
136
2
9
Order By: Relevance
“…This discouraging mid-term outcome has led to the suspension of further keratoprosthesis surgery until something can be done to reduce RPM. It was observed that the eyes that had very severe inflammation (alkaline or acid burns) developed RPM earlier than eyes that had corneal problems such as decompensation from cataract surgery; the finding is similar to that of Yaghonti et al Four out of the five eyes developed 11 RPM under six years. The fifth eye had severe endophthalmitis that made the eye phthysical, but he had no RPM before his endophthalmitis at six years post-operation.…”
Section: Discussionsupporting
confidence: 76%
“…This discouraging mid-term outcome has led to the suspension of further keratoprosthesis surgery until something can be done to reduce RPM. It was observed that the eyes that had very severe inflammation (alkaline or acid burns) developed RPM earlier than eyes that had corneal problems such as decompensation from cataract surgery; the finding is similar to that of Yaghonti et al Four out of the five eyes developed 11 RPM under six years. The fifth eye had severe endophthalmitis that made the eye phthysical, but he had no RPM before his endophthalmitis at six years post-operation.…”
Section: Discussionsupporting
confidence: 76%
“…RPM formation, another predisposing factor to RD in our series, has also been attributed to inflammation 14 and associated with autoimmune disease. 15,16 We have demonstrated a strong correlation among the 3 factors most strongly associated with RD after KPro: sterile vitritis, RPM formation, and history of autoimmune disease. Accounting for these correlations, sterile vitritis and indication for surgery (autoimmune vs local disease) appear to be the only factors strongly predictive for development of an RD.…”
Section: The Role Of Inflammationmentioning
confidence: 76%
“…Glaucoma has been reported to occur in between 58-72% of patients who have received a Boston keratoprosthesis. [77][78][79] In one series of patients with aniridia, 14 of 15 (93%) patients had pre-existing glaucoma. Glaucoma surgery was performed in 4 of 15 (27%) patients before to implantation of the keratoprosthesis.…”
Section: Trabeculectomymentioning
confidence: 99%